An Absolute Paleogeographic Positioning of the Early Permian Tarim Large Igneous Province. Issue 5 (10th May 2020) - Wei, Bitian; Yang, Xingfeng; Cheng, Xin; Domeier, Mathew; Wu, Hanning; Kravchinsky, Vadim A.; Zhou, Yanan; Jiang, Nan; Wu, Yiying; Huo, Feifei; Zhang, Weijie; Zhang, Yichen; et al.
Abstract: This paper presents a quantitative characterization of the early Permian latitude and longitude of the Tarim block and its relationship to the supercontinent Pangea using a combination of newly acquired paleomagnetic data and inferences drawn from the plume generation zone reconstruction method. Early Permian magmatic rocks from Tarim have previously been interpreted as constituents of a large igneous province (LIP) and were therefore possibly derived from a mantle plume originating at the core‐mantle boundary. Here, we present the results of a paleomagnetic investigation of early Permian rocks (~288 Ma) in the Keping area of northwestern Tarim. A stable high‐temperature component (HTC) was isolated from 413 samples from 51 sites. The directions of this HTC pass the fold test and are of exclusively reversed polarity, which is consistent with their acquisition during the late Carboniferous to mid‐Permian Kiaman Reverse Polarity Superchron, suggesting that the HTC is likely primary. From these results, we compute a new early Permian pole for Tarim: 50.1°N, 170.5°E, A 95  = 3.6°. Taking the estimated eruption center of the Tarim LIP (41°N, 80°E) as a reference point, this pole restores the LIP to a paleolatitude of ~30° at 288 Ma. Given this paleolatitude estimate, we attempt to fit the LIP to the edge of one of the large low shear velocity provinces in the lowermost mantle. It is not feasible to reconstruct the Tarim LIP directly above the margins of either the African or Pacific large low shear velocity provinces, but its reconstructed position could potentially be associated with the "Perm" anomaly. Key Points: This paper presents a quantitative characterization of the early Permian latitude and longitude of the Tarim large igneous province (TLIP) We reconstruct Tarim (41°N, 80°E) to a paleolatitude of 29.9°N ± 3.6° at 288 Ma We propose that the TLIP could be related to the Perm anomaly and estimate Tarim's ~288 Ma longitude to be ~55–60°E